Hypertension and immunity: mechanisms of T cell activation and pathways of hypertension. Issue 5 (September 2015) - Abais-Battad, Justine M.; Rudemiller, Nathan P.; Mattson, David L.
Abstract : Purpose of review: The role of immune mechanisms to amplify hypertension in patients and animal models has been appreciated for decades. This review briefly summarizes recent studies exploring the mechanistic pathways, whereby the immune system participates in hypertension and renal disease. Recent findings: Emphasis in this review is placed upon recent studies exploring the role of T cell subtypes, newly described mechanisms of T cell activation, the identification of potential neoantigens, and environmental influences on immune cell activation. Summary: Significant advancements have been made in the search for antigens and pathways responsible for activation of the adaptive immune response, furthering our understanding of the factors contributing to hypertension and potentially leading to the development of new and more effective therapies.